2018
DOI: 10.1177/1071100718806474
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure of Total Ankle Arthroplasty With a Minimum Five Years of Follow-up

Abstract: Background: As the popularity of total ankle arthroplasty (TAA) increases and indications expand, surgeons require a better understanding of which patient factors are associated with implant failure. In this study, we aimed to use a large total ankle database to identify independent risk factors for implant failure at mid- to long-term follow-up. Methods: A prospectively collected database was used to identify all patients who underwent primary TAA with a minimum 5 years’ follow-up. The primary outcome was rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 38 publications
(60 reference statements)
6
77
1
1
Order By: Relevance
“…27,29,30,39 In contrast to other prosthesis designs, survivorship of the Salto Talaris implant was observed to be comparable to that of previously published studies with similar durations of follow-up. 1,6,33 While we cannot claim that this implant is superior to other available implants on the market, our results do demonstrate the continued durability of this particular implant with mid-to long-term follow-up. A recent systematic review comparing outcomes of TAA and arthrodesis over the past decade reported that despite having a lower postoperative complication rate, TAA was associated with an increased rate of reoperations.…”
Section: Discussionmentioning
confidence: 49%
“…27,29,30,39 In contrast to other prosthesis designs, survivorship of the Salto Talaris implant was observed to be comparable to that of previously published studies with similar durations of follow-up. 1,6,33 While we cannot claim that this implant is superior to other available implants on the market, our results do demonstrate the continued durability of this particular implant with mid-to long-term follow-up. A recent systematic review comparing outcomes of TAA and arthrodesis over the past decade reported that despite having a lower postoperative complication rate, TAA was associated with an increased rate of reoperations.…”
Section: Discussionmentioning
confidence: 49%
“…Interestingly, if we had considered only the peak axial force during level walking as has been done by previous investigators, 5,6 the results would have been smaller peak micromotions (Table 3) and smaller amounts of bone at risk of failure (Table 4) We found that the fixation design played an important role in the magnitude of the maximum peak micromotion: the stem design had four to five times larger values (874-1125 µm) than the three spikes and keel designs, for which the peak micromotion was both smaller and similar to one another (~54-140 µm). Moreover, the distribution of micromotion at the instant of the maximum peak micromotion was also dependent on the fixation design: for the three spikes design, the highest micromotion was located posteriorly; for the keel, the highest micromotion was located anteriorly; and the stem design showed a concentric pattern around the stem.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding alignment, studies have been published focusing on the relationship between TAR malalignment and failure of the implant. 12,26 However, no direct correlation between radiographic residual malalignment and onset of PPC has been demonstrated so far.…”
Section: Introductionmentioning
confidence: 99%